EFFICIENCY MODELING STRUCTURES IN TRAINING EXERCISES PLAYER SPECIALIZED EXTREME ITEM TO THE TEAM HANDBALL REPRESENTATIVE SECONDARY SCHOOLS (GYMNASIUM, 2009)
This paper tries to highlight the need to develop specific means of action for individual physicalpreparation of players specializing as an extreme and their planning methodology, in the teams secondaryrepresentative that can easily be adapted by any coach without affect objectives.Aspects of individuality in the preparation of players can be seen from another angle, namely, forthose who evolve extreme position, individualization may know and nuances of individuality in couples ofplayers or groups of players in similar conditions and identical to those of the competition.